Power transistor fault diagnosis in SRM drives based on indexes of symmetry - Amaral, Tito G. (2019)
Pest-E/EEI/LA0021/2014. FCT/MOST Proc. 441. Intergovernmental Science and Technology Innovation Cooperation Special Project of National Key R&D Program of China under 2016YFE0132300.